Efficacy of Ceragenins in Controlling the Growth of Oral Microorganisms: Implications for Oral Hygiene Management - Michał Czarnowski; Monika Słowińska; Mariusz Sawieljew; Urszula Wnorowska; Tamara Daniluk; Grzegorz Król; Maciej Karasiński; Sławomir Okła; Paul B. Savage; Ewelina Piktel; Robert Bucki (MDPI AG, 2024)
Ensuring proper dental hygiene is of paramount importance for individuals' general well-being, particularly for patients receiving medical care. There is a prevailing utilization of conventional oral hygiene items, including toothbrushes and mouthwashes, which have gained widespread acceptance; nevertheless, their limitations encourage investigating novel options in this domain. Our study indicates that ceragenins (CSAs) being lipid analogs of host defense peptides, well-recognized for their wide-ranging antimicrobial properties, may be a potentially efficacious means to augment oral hygiene in hospitalized individuals. We demonstrate that ceragenins CSA-13, CSA-44, and CSA-131 as well as undescribed to date CSA-255 display potent antimicrobial activities against isolates of fungi, aerobic, and anaerobic bacteria from Candida, Streptococcus, Enterococcus, and Bacteroides species, which are well-recognized representatives of microbes found in the oral cavity. These effects were further confirmed against mono- and dual-species fungal and bacterial biofilms. While the ceragenins showed similar or slightly diminished efficacy compared to commercially available mouthwashes, they demonstrated a highly favorable toxicity profile toward host cells, that may translate into better maintenance of host mucosal membrane stability. This suggests that incorporating ceragenins into oral hygiene products could be a valuable strategy for reducing the risk of both oral cavity-localized and secondary systemic infections and for improving the overall health outcomes of individuals receiving medical treatment.